2012
DOI: 10.1007/s11434-012-5466-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous mineralization of CO2 and recovery of soluble potassium using earth-abundant potassium feldspar

Abstract: CO 2 capture and storage (CCS) is an important strategy in combatting anthropogenic climate change. However, commercial application of the CCS technique is currently hampered by its high energy expenditure and costs. To overcome this issue, CO 2 capture and utilization (CCU) is a promising CO 2 disposal method. We, for the first time, developed a promising method to mineralize CO 2 using earth-abundant potassium feldspar in order to effectively reduce CO 2 emissions. Our experiments demonstrate that, after add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
(25 reference statements)
1
22
0
Order By: Relevance
“…Han et al [33] regarded the high temperature reaction as a cation exchange reaction between potassium ions in the silica-alumina-oxygen network structure of K-feldspar and calcium ions in the calcium chloride melt. Recently, Xie et al [34] and Ye et al [35] proposed a novel approach for the simultaneous extraction of potassium via the calcination of A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Han et al [33] regarded the high temperature reaction as a cation exchange reaction between potassium ions in the silica-alumina-oxygen network structure of K-feldspar and calcium ions in the calcium chloride melt. Recently, Xie et al [34] and Ye et al [35] proposed a novel approach for the simultaneous extraction of potassium via the calcination of A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our previous studies (Xie et al 2013b;Ye et al 2014) revealed that wollastonite (CaSiO 3 ), pseudowollastonite (Ca 3 Si 3 O 9 ), Cl-mayenite (Ca 12 Al 14 O 32 Cl 2 ), anorthite (CaAl 2 Si 2 O 8 ), and quartz (SiO 2 ) are the main components in the potassium-depleted residue. Theoretically, all the Cabearing phases in the residue can be utilized for CO 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
“…wollastonite, olivine) in a proper humidity may interact with high-purity CO 2 in a comparatively short time. Additionally, a new framework has been suggested for CO 2 capture and utilization (CCU), under which the captured CO 2 is taken as initial material to gain high-value products thus reducing CO 2 emissions (Xie 2010a, b;Xie et al 2012aXie et al , b, 2013.…”
Section: Introductionmentioning
confidence: 99%